Strategies for Tourism Development in National Parks with the Use of Swot Model (Case: Golestan National Park) - Bazzi, Khodarahm; Khoshfar, Gholam Reza; Zadeh, Hossein Mousa (International Journal of Geography and Geology, 2014)
Nowadays, tourism industry is one of the important sources of production, income, occupation and building infrastructure to achieve sustainable development. In addition many of the policy makers and development planners reminded it as a main pillar of sustainability. According to this, tourism in national parks is considered as an important dimension of tourism. Due to this, there is a question here which is what are the potentials and tourism limitations in national parks? And how can we use the strategies to improving the tourism development in national parks which causing the tourism growth and also the national development? According to this , the present article by using the field studies, determining the strength and weaknesses, opportunities and threats is offering strategies and solutions in order to tourism development in Golestan National park. The achieved results of SWOT method showed that the mentioned area has vast capabilities in tourism which requiring attention and appropriate planning in this area.